Photocontrolled Terahertz Amplified Modulator via Plasma Wave Excitation in ORTD-Gated HEMTs - Changju Zhu; Luhong Mao; Fan Zhao; Xurui Mao; Weilian Guo (IEEE Photonics Journal, 2017)
This paper theoretically explores photocontrolled terahertz amplified modulator in electron plasma wave optically switched resonant tunneling diode (ORTD) gate high-electron mobility transistor. We present a developed distributed circuit model based on the Khmyrova model. Photoexcitation causes ORTD operating state between negative differential conductivity and positive differential conductivity, which power gain of the device can be control by photoexcitation. Numerical and analytical results show that photoexcitation enabling amplified modulator can realize much larger modulation depth (>95%) than what has been reported in photocontrolled modulator. Our results show the potential of this device in several fields of terahertz technology, such as photocontrolled modulator, mixer, and other two port networks.